Housing care of the elderly people in Slovenia: homes for the elderly and owner-occupied dwellings - Kerbler, Boštjan (Journal for Geography, 2012)
Ageing of population raises many problems concerning adequate housing for the elderly. In Slovenia there are several residential types for the elderly and among them the article focuses on two, which are most widespread, homes for the elderly and owner-occupied dwellings. Their characteristics are presented, the problems are critically analyzed and the solutions for them are stated. The article is based on an analysis of relevant sources and scholarly literature, as well as results of scientific researches on this topic. Through its discussion the article reflects new ideas about the possibilities of providing an adequate level of housing care of the elderly people in Slovenia in the future.
Keywords: ageing population; elderly people; housing; housing care; homes for the elderly; owner-occupied dwellings